2017
DOI: 10.1002/itl2.6
|View full text |Cite
|
Sign up to set email alerts
|

Establishing personal trust‐based connections in distributed teams

Abstract: Trust is a factor that dramatically contributes to the success or failure of distributed software teams. We present a research model showing that social communication between distant developers enables the affective appraisal of trustworthiness even from a distance, thus increasing project performance. To overcome the limitations of self‐reported data, typically questionnaires, we focus on software projects following a pull request‐based development model and approximate the overall performance of a software p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…Furthermore, the results of the logistic regression show that more open developers are more likely (+36%) to contribute commits that are successfully integrated into a project repository. This finding complements the results of our previous work [86,87], where we found that more agreeable integrators are more likely to accept the pull requests during code review sessions. Agreeableness, in fact, is associated with the propensity to trust other, being empathetic, and avoiding harsh confrontations -facets of personality that are 'helpful' during cooperative tasks such as code reviews, where more open/agreeable contributors and integrators are likely to collaborate with less friction.…”
Section: Personality and Extent Of Contribution (Rq4 Rq5 Rq6)supporting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, the results of the logistic regression show that more open developers are more likely (+36%) to contribute commits that are successfully integrated into a project repository. This finding complements the results of our previous work [86,87], where we found that more agreeable integrators are more likely to accept the pull requests during code review sessions. Agreeableness, in fact, is associated with the propensity to trust other, being empathetic, and avoiding harsh confrontations -facets of personality that are 'helpful' during cooperative tasks such as code reviews, where more open/agreeable contributors and integrators are likely to collaborate with less friction.…”
Section: Personality and Extent Of Contribution (Rq4 Rq5 Rq6)supporting
confidence: 90%
“…On the one hand, these results are not surprising; in fact, they are in line with the results of both RQ4 (i.e., no differences in mean personality traits score among developers when grouped by activity level) and prior work that uncovered the technical antecedents of accepted contributions in OSS projects (e.g., [120,121]). On the other hand, combined with the findings from our previous work on trust [86,87] and RQ5 (i.e., more open developers are more likely to contribute), these results suggest that personality may have an impact on development activities that entail direct communication with others, as in code review tasks. Still, given the marginal fit and the cross-sectional nature of the data fed into the regression models,here we can only hint at possible causal relations, which we reserve to investigate in future work.…”
Section: Personality and Extent Of Contribution (Rq4 Rq5 Rq6)supporting
confidence: 58%
See 3 more Smart Citations